2015
DOI: 10.1007/s00264-015-3018-x
|View full text |Cite
|
Sign up to set email alerts
|

Varus-valgus stress radiograph as a predictor for extensive medial release in total knee arthroplasty

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, when aHKA is higher or lower than the vcHKA, this suggests medial collateral ligament has changed length either through attenuation or ibrosis. These indings are supported by Lee et al [20] who recently demonstrated that valgus stress x-rays can predict the need for soft tissue release in varus deformity during TKA [1,34]. In these scenarios a functional that accounts for the change in laxity would be required to obtain a well-balanced knee.…”
Section: Discussionmentioning
confidence: 70%
“…However, when aHKA is higher or lower than the vcHKA, this suggests medial collateral ligament has changed length either through attenuation or ibrosis. These indings are supported by Lee et al [20] who recently demonstrated that valgus stress x-rays can predict the need for soft tissue release in varus deformity during TKA [1,34]. In these scenarios a functional that accounts for the change in laxity would be required to obtain a well-balanced knee.…”
Section: Discussionmentioning
confidence: 70%
“…8 While, Ahn et al and Lee et al demonstrated that the significant predictive risk factor of the extensive soft tissue release is the preoperative sum of the mechanical varus and valgus stress angles and preoperative varus-valgus stress angles difference, respectively. 28,33 Also, preoperative distractive stress radiographs were suggested to be a more important risk factor in predicting the extent of soft tissue release in other studies. 26,34 Using additional preoperative stress or distraction radiographs may be effective in predicting the extent of soft tissue release, but it also incurs additional costs and the patient receives more radiation.…”
Section: Discussionmentioning
confidence: 95%
“…6,21,24,25 The preoperative risk factors of the extent of medial release in varus knee during TKA have been evaluated in a few studies, but most of them have focused on the stress or distractive angles and radiographs. 8,26,28,33,34 Moon et al showed that the extent of MCL release had the most significant correlation with the preoperative valgus stress angle. 8 While, Ahn et al and Lee et al demonstrated that the significant predictive risk factor of the extensive soft tissue release is the preoperative sum of the mechanical varus and valgus stress angles and preoperative varus-valgus stress angles difference, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative full-length lower limb radiographs under valgus stress [1,13,17,30] are useful for determining the type of surgery and predicting prognosis for medial knee osteoarthritis (OA) [2,15,19,25,33]. Especially for unicompartmental knee arthroplasty (UKA), they are important for preoperative planning [7,30] because overcorrection might cause lateral tibiofemoral (TF) compartment OA [12,26] and undercorrection might increase the risk of early subsidence of the tibial component after surgery [12,29].…”
Section: Introductionmentioning
confidence: 99%